Inventarisasi sarana dan prasarana obyek wisata di Kota Banjarmasin - Noor Hidayah Pujianti; Ellyn Normelani; Nevy Farista Aristin (Universitas Negeri Malang, 2017)
This article aims to identify, classify and mapping facilities and infrastructure of tourism objects in the city of Banjarmasin. Primary data collection techniques using survey methods, interviews, documentation, and literature study. Secondary data obtained from Tourism Department of Art and Culture and Culture and Tourism Office of South Kalimantan Province. Data analysis technique used is spatial analysis. This study used descriptive qualitative method. The results showed that the facilities and infrastructure of tourism objects in Banjarmasin City for basic facilities, supplementary facilities, and the largest supporting facilities is restaurant / restaurant with the number of 26 pieces or 41.27%, the smallest is the tourist transport and cinema building with each amount 1 fruit or 1.51%. Public infrastructure and public utilities in Banjarmasin are the largest ATMs / Banks with 7 units or 30.43%, the smallest is the power station, the provision of clean water, seaports, and communication facilities with each amounted to 1 piece or 4 , 35%.Keywords: Facilities, Infrastructure, Tourism Objects http://dx.doi.org/10.17977/um022v2i12017p046